1994
DOI: 10.1111/j.1467-6494.1994.tb00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Transference in Interpersonal Relations: Inferences and Affect Based on Significant‐Other Representations

Abstract: Based on an information-processing model of transference and a recent experimental demonstration of transference, defined in terms of "biased inference and memory" (Andersen & Cole, 1990), the present research examined the transfer of affective responses to a new individual, as in schema-triggered affect (Fiske, 1982). Using idiographic stimulus-generation procedures and a nomothetic experimental design, we exposed subjects to a description of a new, unknown person, allegedly seated next door. The description … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
262
4
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(295 citation statements)
references
References 107 publications
27
262
4
2
Order By: Relevance
“…When subsequently asked to describe the characters, participants mistakenly attributed traits to the characters that were part of their schemas of the significant other but were not originally included in the character's description. More recently, Andersen and her colleagues have extended this ingenious experimental paradigm to demonstrate the transference of affect from significant others to descriptions of unknown others allegedly seated next door ( Andersen & Baum, 1994 ). In their latest work, Andersen, Reznik, and Manzella (1996) showed that these affective evaluations lead to differential tendencies to avoid or approach the person next door, demonstrating that transferential processes can influence cognition, affect, and motivation-a central claim of psychoanalytic theory since Freud.…”
Section: The Role Of Mental Representations Of the Self Others And mentioning
confidence: 99%
“…When subsequently asked to describe the characters, participants mistakenly attributed traits to the characters that were part of their schemas of the significant other but were not originally included in the character's description. More recently, Andersen and her colleagues have extended this ingenious experimental paradigm to demonstrate the transference of affect from significant others to descriptions of unknown others allegedly seated next door ( Andersen & Baum, 1994 ). In their latest work, Andersen, Reznik, and Manzella (1996) showed that these affective evaluations lead to differential tendencies to avoid or approach the person next door, demonstrating that transferential processes can influence cognition, affect, and motivation-a central claim of psychoanalytic theory since Freud.…”
Section: The Role Of Mental Representations Of the Self Others And mentioning
confidence: 99%
“…Individuals hold distinct and chronically accessible mental representations of "significant others" and frequently use these representations as templates for interaction with unfamiliar partners (Andersen & Baum 1994, Andersen et al 1996. When a new partner exhibits traits possessed by a significant other, individuals frequently respond to the person in a manner that mirrors responses to the significant other.…”
Section: Information and Interactionmentioning
confidence: 99%
“…This supports the conclusion that hearing about someone who resembles a significant other activates a representation or transference pattern that influences social memories. Andersen and her colleagues also demonstrated that resemblance to a significant other affected, in predicted ways, a subject's conscious mood and feelings about the target (Andersen and Baum 1994;Andersen et al 1995), self-concept (Hinkley and Andersen 1996), facial affect, expectancies, motivation to meet the target (Andersen, Reznik, and Manzella 1996), and even conversation patterns (Berk and Andersen 2000). This was true even when significant-other descriptions were presented subliminally (Glassman and Andersen 1999).…”
mentioning
confidence: 80%
“…We intend to explore and more precisely describe these phenomena using a paradigm developed over the past fifteen years by Susan Andersen, a cognitive and social psychologist at New York University (Andersen and Baum 1994;Andersen and Berk 1998;Andersen and Chen 2002;Berk and Andersen 2000;Glassman and Andersen 1999). This paradigm is guided by the theory that a normal person's perceptions and affective responses vis-à-vis the self and others are heavily influenced by the activation of significant relationship representations from the past.…”
mentioning
confidence: 99%